2018
DOI: 10.1186/s12894-018-0421-9
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of rutin against cisplatin-induced reproductive toxicity in male rats

Abstract: BackgroundCisplatin (CP) or cis-diammine dichloroplatinum (II) is a platinum based standard antineoplastic drug which is used against variety of solid tumors and neoplasms. The present study aimed to evaluate the shielding effects of rutin against CP induced testicular toxicity in rats.Methods28 male rats were divided into four groups. First group was given saline orally while second group received intra-peritoneal (i.p) injection of cisplatin (7 mg/kg) on day first and received saline for next 13 days. Third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 68 publications
7
45
0
Order By: Relevance
“…These histopathological changes were reversed with dose-dependent manner in mice treated with Ficus carica extract. The mentioned results coincide well with the findings of other authors who demonstrated that cisplatin had impaired spermatogenesis and resulted in gonadal dysfunction, altered Leydig cells and antioxidant enzyme status 12 . Also temporary or permanent azoospermia are other forms of side effects associated with cisplatin treatment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These histopathological changes were reversed with dose-dependent manner in mice treated with Ficus carica extract. The mentioned results coincide well with the findings of other authors who demonstrated that cisplatin had impaired spermatogenesis and resulted in gonadal dysfunction, altered Leydig cells and antioxidant enzyme status 12 . Also temporary or permanent azoospermia are other forms of side effects associated with cisplatin treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Like other chemotherapeutic drugs CP possesses many side effects in clinical uses and experimental animal studies. The use of CP for clinical purposes is limited by its side effects 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another cisplatininduced testicular toxicity study it was found that only cisplatin treatment resulted in a significant decrease in daily sperm production, head length and % DNA in head, reduction of epithelial cells height, tubular diameter, number of spermatogonia, spermatocytes and spermatids, the intratesticular testosterone concentrations, increase in the thiobarbituric acid reactive substances (TBARS) and oxidative stress in testicular tissues. Rutin treatment to cisplatin-treated rats resulted in reversing cisplatin's effects on DNA damage, sperm count, histological and biochemical parameters, thus suggesting the shielding effects of rutin against cisplatin-induced testicular toxicity (Jahan et al, 2018). The effects of rutin on diabetic-induced impairments in sexual behaviour, spermatogenesis and oxidative testicular damage have also been reported.…”
Section: Protective Ability Against Testicular Toxicitymentioning
confidence: 89%
“…Several previous studies showed that natural compounds attenuated CSP testicular toxicity [26][27][28]. Some studies revealed that natural compounds provided more protective effect than synthetic compounds [26].…”
Section: Discussionmentioning
confidence: 99%